Higher superstition the academic left and its quarrels with science - Gross, Paul R.; Levitt, Norman (Johns Hopkins Univ. Press, 1994)
With the emergence of "cultural studies" and the blurring of once clear academic boundaries, scholars are turning to subjects far outside their traditional disciplines and areas of expertise. In Higher Superstition scientists Paul Gross and Norman Levitt raise serious questions about the growing criticism of science by humanists and social scientists on the "academic left." As literary theorists deconstruct scientific "texts" and feminists condemn scientific "patriarchy," they argue, principles and practices that underlie 300 years of scientific achievement come under attack from scholars with little actual knowledge of science. Gross and Levitt explore the origins and history of the trend and examine examples of "science bashing" from an array of currently fashionable viewpoints - postmodernism, feminism, radical environmentalism, multiculturalism, and AIDS activism. They find the origins of antiscience attitudes not only in modern discontents but also in a long tradition of Romantic unhappiness with Rationalism. Their concerns, however, are clearly for the present and the future. They question how far the university community should go in validating nonscientific judgments of science. And they warn that the long-term consequences of these trends - for science education and for public judgment of scientific issues - may be infinitely more serious than the "political correctness" wars currently being waged on university campuses.
Keywords: Academici; Exacte wetenschappen; Humanidades; Kritiek (algemeen); Links (politiek); Postmodernisme; Sciences - Aspect social; Sciences et sciences humaines; Sciences humaines - Etude et enseignement (supérieur) - Etats-Unis; Gesellschaft; Naturwissenschaft; Postmoderne; Humanities; Science -- Social aspects; Wissenschaftskritik; Naturwissenschaftler; Kultur; Sozialwissenschaften; Naturwissenschaften; Sozialwissenschaftler; Die Linke; Streit; Linksintellektueller; Irrationalismus; Geisteswissenschaften